2007
DOI: 10.1007/s00421-007-0627-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adrenergic receptors and adrenergic functions in cold adapted humans

Abstract: To specify the role of adrenoceptors in mediating adrenergic functions after adaptation of humans to cold, effect of administration of increasing concentrations of beta1 and beta2 adrenomimetics (Dobutamine, Bricanyl) on resting metabolic rate, heart rate, systolic blood pressure, rectal and skin temperatures of control humans and of cold adapted winter swimmers was studied. Increase in metabolic rate, mediated by beta1 and beta2 adrenomimetics, was attenuated after cold adaptation, indicating downregulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…In this study we used cold as an acute stressing agent, considering that when exposed for long term (more than 1 month) it is observed an adaptation mechanism [10][11][12]. According to Janský et al [13], the chronic exposure to extreme low temperatures would not decrease cardiomyocytes nuclear size such as we found in our study due to the adjustment condition. Based on our data, we believe that the acute hypothermic exposure causes opposite effects compared to the chronic exposure to cold.…”
Section: Discussionsupporting
confidence: 49%
“…In this study we used cold as an acute stressing agent, considering that when exposed for long term (more than 1 month) it is observed an adaptation mechanism [10][11][12]. According to Janský et al [13], the chronic exposure to extreme low temperatures would not decrease cardiomyocytes nuclear size such as we found in our study due to the adjustment condition. Based on our data, we believe that the acute hypothermic exposure causes opposite effects compared to the chronic exposure to cold.…”
Section: Discussionsupporting
confidence: 49%
“…Surprisingly, CA does not affect the initial rise of noradrenaline or adrenaline concentrations in plasma (Lesná et al, 1999). However, down-regulation of adrenergic receptors in CA subjects (Jansky et al, 2008) may influence the final response to cold. A decrease in core temperature in cold is prevented by increasing heat production, i.e.…”
Section: Discussionmentioning
confidence: 87%
“…Only one study (De Lorenzo et al, 1998) has reported significant reduction of total and LDL cholesterol levels in a group of hypercholesterolaemic patients after 90 days of cold adaptation. Increased catecholamine secretion or altered sensitivity of catecholamine receptors could explain the decrease of total and LDL cholesterol after cold adaptation (De Lorenzo et al, 1998;Jansky et al, 2008). However, the opposite effect of corticosteroids should also be taken into account (Hermanussen et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…1997). Studies on humans confirm the relative role played by β 1 and β 2 adrenergic receptors in the determination of the basal metabolic rate, with β 1 being the most relevant isoform (Jansky 1995, Jansky et al . 2008).…”
Section: Introductionmentioning
confidence: 89%